2019
DOI: 10.1038/s41598-019-53017-4
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of End-Stage Renal Disease in Psoriatic Patients: Real-World Data from a Nationwide Population-Based Cohort Study

Abstract: Psoriasis is a chronic inflammatory skin disorder mediated by the T-cell–related immune response. Psoriatic patients may have a variety of comorbidities, but their risk of end-stage renal disease (ESRD), particularly according to the subtype of psoriasis, is unclear. We investigated the risk of ESRD in patients with psoriasis according to the subtype of psoriasis and history of systemic therapy for psoriasis. A total of 2,121,228 adults (1,590,921 in the control group and 530,307 in the psoriasis group) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Additional evidence about the role of the Th17/IL-17 axis on Kidney diseases comes from the observation of the increased risk of CKD associated with renal inflammation in human diseases that occur with the hyperactivation of the Th17/IL-17 axis, like psoriasis (210)(211)(212), rheumatoid arthritis (213,214), and ankylosing spondylitis (215)(216)(217). In two studies (in the United Kingdom and Taiwan), psoriasis was associated with an increased risk of chronic kidney disease independent of traditional risk factors (211,212).…”
Section: The Association Between Th17/il-17 Axis Hyperactivity and Several Kidney Diseases (Other Than Lupus Nephritis)mentioning
confidence: 99%
“…Additional evidence about the role of the Th17/IL-17 axis on Kidney diseases comes from the observation of the increased risk of CKD associated with renal inflammation in human diseases that occur with the hyperactivation of the Th17/IL-17 axis, like psoriasis (210)(211)(212), rheumatoid arthritis (213,214), and ankylosing spondylitis (215)(216)(217). In two studies (in the United Kingdom and Taiwan), psoriasis was associated with an increased risk of chronic kidney disease independent of traditional risk factors (211,212).…”
Section: The Association Between Th17/il-17 Axis Hyperactivity and Several Kidney Diseases (Other Than Lupus Nephritis)mentioning
confidence: 99%
“… Indicators of renal impairment are higher in psoriasis patients: urinary albumin excretion rate and microalbuminuria 71,72 Psoriasis patients had a higher risk of developing ESRD ( p < .001) after adjusting for age, gender, household income, region, diabetes, hypertension, and dyslipidemia 73 Duration and severity of psoriasis correlated positively with the ratio of urinary albumin to creatine 74 …”
Section: Resultsmentioning
confidence: 99%
“…Psoriasis patients had a higher risk of developing ESRD ( p < .001) after adjusting for age, gender, household income, region, diabetes, hypertension, and dyslipidemia 73 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study has shown that proteinuria is significantly associated with psoriasis [ 12 ]. In addition, psoriasis increases the risk of CKD or end-stage renal disease [ 13 , 14 ]. However, whether proteinuria affects the development of psoriasis is unknown.…”
Section: Introductionmentioning
confidence: 99%